PREVALENCE OF ASYMPTOMATIC PERIPHERAL ARTERIAL DISEASE AND ITS ASSSOCIATION WITH AGE AND GENDER IN TYPE 2 DIABETES MELLITUS IN A TERTIARY CARE TEACHING HOSPITAL: A CROSS-SECTIONAL STUDY - THAKKAR, SHRIJIKUMAR C; TANNA, PURVI J; BAGHEL, RUCHI; ADWAL, SANDEEP KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The true prevalence of peripheral arterial disease (PAD) in individuals with diabetes has been difficult to determine because of the lack of symptoms and insensitive diagnosis. We estimated the prevalence of PAD and its association with age and gender in Type 2 diabetes mellitus (DM) who were asymptomatic for PAD. Methods: Total 150 Type 2 DM patients were screened and examined for PAD using Ankle Brachial Index and Color Doppler. Prevalence of PAD was further studied and statistically analyzed to find its association with age and gender. Results: Prevalence of PAD in our study was 16%. Out of total 150 Type 2 DM patients, 24 patients were diagnosed to have PAD by Color Doppler. The prevalence was 12.0% in the fifth and sixth decade followed by 3.3% in seventh and eighth decade and 0.7% in <40 years age group. Out of total 150 cases, there were 83 males and among them 15 (18.1%) had PAD and out of 67 females, 9 (13.4%) had PAD. After application of Chi-square test to the above observations, there was no statistically significant association of age and gender with PAD in our study population. Conclusion: In the present study, the prevalence of PAD was 16%; 10% and 6% in males and in females, respectively. There was no statistically significant correlation of PAD with age and gender.